Study of Light and Heavy Minerals and Their Effect on Oil Aggregation in the Zubair Formation for the Rumaila Oil Field in Southern Iraq - Al- Humaidan, Zainab A.; Al-Jaberi, Mohanad H.; Al-Mayyahi, Haider K.; Al-Mutouri, Zainab A. (Iraqi Journal of Science, 2022)
Zubair Formation is the most productive reservoir in southern Iraq, which is comprised of sandstones, interbedded with shale sequences and sometimes carbonate rock. It is an important formation in the lower Cretaceous cycle in Iraq. Rumaila oil field is the largest oil field in Iraq and the 6th in the world. Two wells were studied for three depths, one in the southern Rumaila and the other in the north. The study focused on light and heavy minerals in sand fractions and their relationship with hydrocarbon assemblages. For the survey to be complete, the sedimentological study of the cores was also conducted. This research aims to determine the effect of the amount of heavy and light minerals on the generation and production of oil in the reservoir layers.  The sedimentological results were the prevalence of sand for all depths, especially in Southern Rumaila. The sand ratio ranged from 62% to 98%. The rate of heavy minerals in southern Rumaila was greater than in Northern on average at 1.17%. Light minerals were the most in Northern Rumaila up to 99.3% represented in quartz with a high percentage and a little part of feldspar represented in orthoclase. Heavy minerals were represented in Opaque (24%), zircon (27.6%), tourmaline (18%), rutile (11%), biotite (3%), chlorite (3.6%), muscovite (3.6%), staurolite (2%) and hornblende (3.6%). The proportion of quartz was the most in light minerals. The average of minerals is ultra-stable, and Opaque is the most dominant over the other minerals. Ultra-stable minerals in the sand that contain hydrocarbon assemblage are an index to mineralogical maturity for sandstone rocks. The SEM images showed deformations in quartz grains due to the high energy; on the other hand, the roundness and sphericity of the grains were evident, especially in Southern Rumaila sands.